The Effectiveness of Augmented Reality in Teaching English Vocabulary to Seventh-Grades Students - Iisra Kurnia; Riswanto Riswanto; Reko Serasi (Yayasan Sembilan Pemuda Indonesia, 2025)
Mastering vocabulary is a significant challenge for English as a Foreign Language (EFL) learners in Indonesia. Students often face difficulties in mastering vocabulary due to low engagement and the limitations of traditional teaching methods. This study addresses the problem by examining the use of Augmented Reality (AR) in vocabulary instruction. A true-experimental design was employed, involving two groups: an experimental group taught using AR media and a control group taught through traditional methods. A total of 64 students participated in this study. Data were collected through pre-tests and post-tests and analyzed using descriptive statistics, normality and homogeneity tests, paired sample t-tests, and N-Gain analysis. The findings showed that the average post-test score of the experimental group (89.00) was higher than that of the control group (78.56). The N-Gain score in the experimental group (63.28%) also indicated a higher level of improvement compared to the control group (5.66%). The results of the t-test analysis showed a significance value of 0.000 (< 0.05), which means that there was a statistically significant difference between the two groups. These findings suggest that Augmented Reality is an effective and engaging tool for improving students’ vocabulary mastery in English learning. The study recommends incorporating AR technology into vocabulary instruction to enhance student engagement and learning outcomes.